PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN REGULASI TERHADAP PENERAPAN ANGGARAN KOPERASI - Komang Adi Kurniawan Saputra; Gede Mandirta Tama (Jurnal Riset Akuntansi, 2017)
The objective of this study is to examine the influence of human resource competency and regulation implementation on the budgeting implementation at the cooperative in Buleleng regency, Bali Province. The population in this research is cooperative in Buleleng Regency, Bali Province as many as 283 cooperatives. Based on random sampling technique of slovin formula this study obtained 74 cooperatives as the sample of this study. The number of respondents in this study are 222 respondents consist of people directly inolved in the cooperatives management such as Supervisors, Management and Members of Cooperatives. Based on multiple regression analysis, this study found that human resource competency and regulation implementation has significant influence on the budgeting implementation.